Hubungan Penggunaan Smartphone dengan Tingkat Prestasi Belajar Siswa Di SMK Muhammadiyah Cawas - Sri Wahyuni; Piscolia Dynamurti Wintoro (INVOLUSI: Jurnal Ilmu Kebidanan, 2020)
The use of a smartphone is an activity using the features available on a smartphone. Smartphones can be used to study anywhere and make it easier to find or add information. Learning achievement is the maximum result achieved by a person after carrying out learning efforts. Factors that can affect learning achievement can be classified into two parts, namely internal factors, namely physiological aspects (which are physical) and psychological aspects (which are spiritual in nature) and factors. external. This study aims to determine the extent of the relationship between smartphone use and the level of learning achievement of students at SMK Muhammadiyah Cawas. This research method uses descriptive correlational with cross sectional approach. The population in this study amounted to 403 students. The number of samples was taken based on purposive sampling technique, namely 33 students and Kendall tau statistical test. The results showed that 1 student (3.03%) had a high level of good learning achievement. Students with good learning achievement were 18 students (54.55%), only 13 students (39.39%). The conclusion in this study is that there is no relationship between the use of smartphones and the level of student achievement at SMK Muhammadiyah Cawas with p = 0.826 (p> 0.05). Suggestions for students to use smartphones wisely.